PELATIHAN MATERIAL FLOW COST ACCOUNTING (MFCA) BAGI PARA UMKM DI DKI JAKARTA - Virna Sulfitri; Henik Hari Astuti; Budi Santosa (ASOSIASI IDEBAHASA KEPRI, 2022)
Community Service is one part of the direct contribution from academics, in this case the Faculty of Economics and Business, Trisakti University to the community. On this occasion the Trisakti University FEB team had the opportunity to provide training on Material Flow Cost Accounting (MFCA) for MSMEs. This training is considered important considering that the understanding of MSME actors in terms of the flow cost of material is still very minimal, so that in the implementation of their business there are still very few who apply it in the production process. This training aims to educate MSME actors in terms of flow cost accounting for the use of their production materials, MSMEs can sort out the types and types of materials to be used so as to increase the effectiveness and efficiency of production to increase sales and business profits. PKM training will be carried out using an online method considering the conditions of the COVID-19 pandemic, which until now has not allowed face-to-face/off-line training. The output of this PKM will be published to the public so that it can provide wider benefits.